Comparison of Linezolid and Vancomycin for Methicillin-resistant Staphylococcus aureus Pneumonia: Institutional Implications - Tong, ManShan C. (Pharmacotherapy, 2016)
OBJECTIVE: Recent studies suggesting clinical superiority of linezolid over vancomycin in the treatment of methicillin-resistant Staphylococcus aureus (MRSA) pneumonia led to a change in our institution’s clinical pathway/order form for hospital-acquired pneumonia, positioning linezolid as the preferred agent. Our objective was to assess the impact of this change within our institution. DESIGN: Retrospective electronic medical records review METHODS: The analysis for this observational study included eligible patients admitted to our medical center between May 1, 2011 and August 31, 2014 , with ICD-9 codes for MRSA and pneumonia. Included patients were at least 18 years of age and had vancomycin or linezolid initiated at least 2 days after admission and continued for at least 2 consecutive days. The primary endpoints were extent of antibiotic use before and after order form change and length of stay (LOS) and hospital charges in the two treatment groups. A secondary aim was to detect any gross discrepancies in patient outcomes such as treatment duration, mechanical ventilation duration, all-cause mortality rate, nephrotoxicity, and 30-day readmission between the two treatment groups. MEASUREMENTS AND MAIN RESULTS: Outcomes in 227 patients were assessed. Linezolid use increased 16.2% subsequent to the change in the order form. Although not statistically significant, the median hospital admission charge was $6,200 lower in patients treated with linezolid compared with those treated with vancomycin ($25,900 vs. $32,100). Hospital LOS was significantly associated with Charlson comorbidity index (P < 0.001), the type of treatment (p = 0.032), duration of treatment (p < 0.001), mechanical ventilation (p < 0.001), and ICU admission (p < 0.001). All-cause mortality favored linezolid treatment and these patients were more likely to be discharged (shorter LOS). CONCLUSIONS: Although linezolid use increased markedly with this pathway/order form change, no negative institutional consequences or unfavorable patient outcomes were detected, justifying the change in policy from these perspectives.